An experimental verification system for electric vehicle and grid interactive charging safety - Han, Jun; Fan, Anjie; Cai, Chao; Pan, Wenjie; Chen, Haofei (Frontiers in Energy Research, 2024)
The development of electric vehicles (EVs) reduces dependence on fossil fuels, promotes energy conservation and emissions reduction, and facilitates the transition to clean energy sources in the power grid. However, subjective charging behavior among EV owners can lead to blind charging practices, compromising the reliability of the distribution network by widening the peak-to-valley difference. To address safety concerns during the charging process, this paper proposes hardware and software systems for an experimental verification system. The network architecture, focused on charging safety, is examined. Analysis of the system's operation data reveals that it enables bidirectional interaction between electric vehicles and the power grid. This solution proves ef-fective for integrating a large number of EVs in peak-shaving and valley-filling efforts, laying a technical foundation for their inclusion in the power grid for peak shaving, valley filling, as well as providing standby and frequency regulation services.